Teachers' Literacy Motivation as A Learning Support in Merdeka Curriculum - Yuni Susilowati; Arti Prihatini (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2026)
Teachers are role models for students, including in literacy activities. Teachers' literacy habits are among the supports for student literacy. This condition requires teachers to carry out literacy activities to support the implementation of the Merdeka Curriculum.  Based on this, the study aims to describe teachers' motivation for literacy at SMPN 5 Probolinggo in relation to the Merdeka Curriculum. This study uses a narrative inquiry approach, with data collected through in-depth interviews. The subject of the study is an Indonesian language teacher at SMPN 5 Probolinggo. Purposive sampling was used to select the research subjects. The results of the study show that literacy motivation is supported by teachers' competence, particularly in personality, pedagogical, and professional competence. Literacy activities support teachers' roles as role models, in learning preparation, and in professional development for implementing the Merdeka Curriculum. However, social competence has not been explicitly identified in the participants' narratives, so literacy motivation is better understood as a matter of personal responsibility and learning. On the other hand, factors that inhibit teachers' motivation to develop literacy are administrative burden, age, and health conditions. These findings indicate that the motivation for teacher literacy at SMPN 5 Probolinggo is implemented through the development of teachers' competence in personal, pedagogical, and professional domains. However, it still needs to be optimized by addressing social aspects, reducing administrative burdens, and improving physical conditions.